2003
DOI: 10.1253/circj.67.203
|View full text |Cite
|
Sign up to set email alerts
|

Embolic Attack in Patients With Atrial Fibrillation and Atrial Thrombus Depends on the Character of the Thrombus.

Abstract: It is very important to prevent embolisms from left atrial thrombi (LAT). The present study was a trial for the management of patients with AT using 122 patients with atrial fibrillation and LAT who were followed for 1 year after transesophageal echocardiography. LAT were classified by their shape and mobility into the mobile ball type (MB, n=28), fixed ball type (FB, n=32) and mountain type (MO, n=42). The patients were given warfarin (INR: 1.5-2.0, n=43), aspirin 81 mg (n=74) and/or ticlopidine 200 mg/day (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 18 publications
(7 reference statements)
0
18
2
Order By: Relevance
“…4 LAA thrombus is an important source of embolic stroke. Understanding of its complex and extremely variable structure and careful observation of the echocardiographic appearance of the thrombus formation, may provide valuable supplementary information for the evaluation and management of thromboembolic events.…”
Section: Images In Cardiovascular Medicinementioning
confidence: 99%
“…4 LAA thrombus is an important source of embolic stroke. Understanding of its complex and extremely variable structure and careful observation of the echocardiographic appearance of the thrombus formation, may provide valuable supplementary information for the evaluation and management of thromboembolic events.…”
Section: Images In Cardiovascular Medicinementioning
confidence: 99%
“…1) The structure of the LAA is a rod-shaped pouch that may have stagnant blood flow, leading to hemostasis. 1) Abe et al 4,5) reported that LAA thrombi could be classified into three types: the mobile ball type, fixed ball type, and mountain ball type. The mobile ball type is associated with an especially high risk of embolism.…”
Section: Case Reportmentioning
confidence: 99%
“…However, it is sometimes difficult to make a diagnosis because of the splashing and vanishing of the intracardiac source of the emboli. [4][5][6][7][8][9][10][11][12] In patients with cardioembolic stroke it is necessary to carefully examine the intracardiac hypercoagulable state based on echocardiographic findings and/or serum sensitive markers, and then use this information to prevent recurrent attacks.It is well known that the left atrial appendage (LAA) is a major thromboembolic source in cardioembolic stroke. 7,8 Many clinical reports have shown a close relationship between LAA thrombus formation and left atrial mechanical remodeling, based on echocardiographic findings such as the presence of spontaneous echo contrast or a progressive Circulation Journal Vol.70, August 2006 reduction in LAA emptying flow velocity.…”
mentioning
confidence: 99%
“…7,8 Many clinical reports have shown a close relationship between LAA thrombus formation and left atrial mechanical remodeling, based on echocardiographic findings such as the presence of spontaneous echo contrast or a progressive Circulation Journal Vol.70, August 2006 reduction in LAA emptying flow velocity. 6,10,12,13 Serum fibrin monomer (FM) is a precursor of the fibrin polymer that is produced by the thrombin-mediated resolution of fibrinopeptide A from fibrinogen. In vivo, compared with fibrin polymer and stable fibrin, FM is fragile as a result of fibrinolysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation